Case Report: An Extremely Rare Case of Epitheloid Type Leiomyoma - Mokhamad Zhaffal; Shazia Tariq; Anastasia Salame (Case Reports in Oncological Medicine)
Conclusion: Uterine leiomyomas are a common pathology of the uterus that can be confused with malignant tumors, especially in the setting of unusual growth patterns such as the epitheloid leiomyomas. Definitive management involves myomectomies with regular follow-up with favourable prognosis. It is important to properly manage these cases to avoid the overdiagnosis and mistreatment not to mention the repercussion of false diagnoses on the patient’s mental health and well-being.